Becoming and belonging in interdisciplinary PhD research: Supervising across boundaries - Gullbekk, Eystein (Septentrio Conference Series, 2020)
PhD research has been depicted as a process of belonging and becoming. Through information-related activities, such as looking for, finding, avoiding or citing literature, PhD-students connect with people and texts that possess cognitive authority within their discipline or domain. It is assumed that supervisors in the discipline are the most important figures as regards the modelling of PhD-students scholarly identities. For instance, a widely cited textbook on doctoral writing states that “PhD students’ writing is shaped by discipline-specific conventions and protocols; by conversations with advisors who literally embody the discipline” (Kamler and Thomson, 2008, p. 508, cited in Gullbekk & Byström, 2019, p.20). The role of the library and the librarians may well be to facilitate discipline or domain specific information-related activities. In interdisciplinary environments however, PhD-students may experience a process of becoming without belonging and the domain-based cognitive authority of texts and authors may be negotiable. In this round-table, we will explore the role of the library in interdisciplinary PhD-research. First, we will familiarize ourselves with select views on interdisciplinarity and reflect on variations among the roundtable-participants’ interdisciplinary experiences. Second, and more importantly, we will discuss complexities that occur in scholarly communication in a multi-disciplinary research environment where the students write article-based dissertations. We will explore the role of supervisors, librarians included, in a particular case where students must draw on multiple fields or disciplines, where questions of the cognitive authority of texts and of PhD-students’ belonging emerge as somewhat contested. The case discussed in the round table is based on fieldwork conducted in an interdisciplinary department at a Scandinavian University. Participants may familiarize themselves with the case by reading the article Becoming a scholar by publication – PhD students citing in interdisciplinary argumentation (Gullbekk & Byström, 2019).